Wideband metamaterial perfect absorber using topological insulator material for infrared and visible light spectrum: a numerical approach - Vishal Sorathiya; Zen A. Sbeah; Ahmad Alghamdi; Amar Y. Jaffar; Abdullah G. Alharbi (Scientific Reports)
Abstract This study utilises simulations to investigate the potential of a novel multi-layered topological insulator-based wideband absorber design. The proposed design is constructed with a multilayer structure that incorporates meticulously chosen materials to enhance light absorption. The top layer is composed of a metal (Fe/Ti/Cu/Zn/Ag/Au), which is followed by an insulating layer (Si/SiO₂/InP) and a topological insulator (Bi₁.₅Sb₀.₅Te₁.₈Se₁.₂). These layers are sandwiched between two metal layers (Fe/Ti/Cu/Zn/Ag/Au). The proposed structure is analysed for two different resonator-based designs, considering both the L-shaped metal resonator and the complementary L-shaped resonator for the overall computational analysis. The overall structure is computed for the broad range of the wavelength spectrum (0.2–1.6 μm). The proposed metamaterial design achieves an absorption rate of ~ 99% across multiple wavelength bands. This structure also investigated the different parametric values, such as physical dimensions and oblique angle of incident, to identify the optimised values of the different parameters. The metamaterial parameters, such as permittivity, permeability, refractive index, and impedance values, are also investigated over the entire wavelength spectrum, which suggests that the overall structure behaves as a double negative material. The wideband metamaterial structure with topological insulator material can also be compared with the interference mode theory.